2021
DOI: 10.1002/ptr.7081
|View full text |Cite
|
Sign up to set email alerts
|

The effects of flaxseed supplementation on metabolic syndrome parameters, insulin resistance and inflammation in ulcerative colitis patients: An open‐labeled randomized controlled trial

Abstract: The present study aimed to evaluate the efficacy of flaxseed supplementation in the management of metabolic syndrome (MetS)-related parameters among the patients with mild-to-moderate ulcerative colitis (UC). A randomized controlled clinical trial was conducted on 70 patients with UC. Participants were randomized in the intervention group, which received 30 g/day ground flaxseed powder or control group.Anthropometric and biochemical variables were assessed at the beginning and end of 12 weeks of intervention. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 53 publications
0
10
0
1
Order By: Relevance
“…Totally, 2427 subjects were included (case = 1220; control = 1207), and the dates of publications were between 1999 and 2021. Among the 33 studies, 28 were parallel studies, 10,13–16,27–49 and five were crossover 50–54 studies. The intervention duration ranged from 3 to 48 weeks and the sample size varied from 14 to 189 individuals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Totally, 2427 subjects were included (case = 1220; control = 1207), and the dates of publications were between 1999 and 2021. Among the 33 studies, 28 were parallel studies, 10,13–16,27–49 and five were crossover 50–54 studies. The intervention duration ranged from 3 to 48 weeks and the sample size varied from 14 to 189 individuals.…”
Section: Resultsmentioning
confidence: 99%
“…BMI at baseline ranged from 23 to 32 kg m −2 . Studies were conducted in the following countries: Canada, 39,40,42,47,49,50,52 Iran, 14,15,28,29,32–38 China, 10,30,43,53 India, 13,45,46 Brazil, 27,31 Australia, 44 Finland, 54 Denmark, 51 USA, 41 Netherlands, 48 and Cuba. 16…”
Section: Resultsmentioning
confidence: 99%
“…The content of K in flaxseed flour was twice that of wheat flour, and the content of Ca and Mg was more than 10 times that found in wheat flour. In addition, flaxseed flour with a high K/Na ratio is good for patients with hypertension, which may indicate how flaxseed can reduce the incidence of cardiovascular and cerebrovascular diseases ( Morshedzadeh et al, 2021 ). Therefore, it can be concluded that flaxseed flour was an optimal dietary supplement for its contribution to the unsaturated fatty acids and minerals of full flour CSB.…”
Section: Resultsmentioning
confidence: 99%
“…Phenolic compounds are important secondary plant metabolites that help promote the health of crops and foods. TPC and TFC are significant nutrients in flaxseed flour ( Morshedzadeh et al, 2021 , Yari et al, 2021 ). The concentrations of TPC, TFC, DPPH•, ABTS+•, and FRAP in CSB are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation